Sexual and Apogamous Species of Woodferns Show Different Protein and Phytohormone Profiles - Fernández, Helena; Grossmann, Jonas; Gagliardini, Valeria; Feito, Isabel; Rivera, Alejandro; Rodríguez, Lucía; Quintanilla, Luis G.; Quesada, Víctor; Cañal, Mª Jesús; Grossniklaus, Ueli (Frontiers in Plant Science, 2021)
The gametophyte of ferns reproduces either by sexual or asexual means. In the latter, apogamy represents a peculiar case of apomixis, in which an embryo is formed from somatic cells. A proteomic and physiological approach was done in the apogamous fern Dryopteris affinis ssp. affinis and its sexual relative D. oreades. The proteomic analysis compared apogamous vs. female gametophytes, whereas the phytohormone study included, in addition to females, three apogamous stages (filamentous, spatulate and cordate). The proteomic profiles revealed a total of 879 proteins and, after annotation, different regulation was found in 206 proteins of D. affinis and 166 of its sexual counterpart. The proteins upregulated in D. affinis are mostly associated to protein metabolism (including folding, transport and proteolysis), ribosome biogenesis, gene expression and translation, while in the sexual counterpart they account hugely for starch and sucrose metabolism, generation of energy and photosynthesis. Likewise, ultra-performance liquid chromatography-mass spectrometry (UHPLC-MS/MS) was used to assess the levels of indol-3-acetic acid (IAA), the cytokinins BA, t-Z, RZ, DHZ, DHZR, iP, iPA, abscisic acid (ABA), the gibberellins GA3 and GA4, salicylic acid (SA) and the brassinosteroids epibrasinolide (EPI) and castasterone (BK). AIA, the cytokinins Z, RZ, IPA, the gibberellin GA4, the brassinosteoids castasterone, and ABA accumulated more in the sexual gametophyte than in the apogamous one. When comparing the three apogamous stages, BA and SA peaked in filamentous, GA3 and EPI in spatulate and DHRZ in cordate gametophytes. The results point out the existence of deeply metabolic differences between apogamous and sexual gametophytes, and invite to consider the fern gametophyte as a good experimental system to deepen on plant reproduction.